Making electronic contracting operational and trustworthy - Joana Urbano (2010)
An Electronic Institution includes a normative environment with rules and norms for agents' interoperability, and is also a service providing platform that assists agents in the task of establishing and conducting normative relationships (contracts). Using this platform, agents representing organizations willing to engage in a collective contractual activity select partners according to different factors, including their capabilities, current business needs and information on past business experiences that may be used as inputs to trust building. In our framework we have designed a tightly coupled connection between electronic contract monitoring and a computational trust model. In this paper, we explain the rationale behind this connection and detail how it is materialized. In particular, we explain how our situation-aware trust model relies on past contractual behavior to dynamically build up a trustworthiness image of each agent that can be helpful for future encounters. Experiments with simplified scenarios show the effectiveness of our approach.